STRATEGI PENANAMAN SIKAP PEDULI LINGKUNGAN MELALUI PEMBELAJARAN IPA UNTUK SISWA SMP - Virarasari, Lucy; Erman, Erman (Program Studi S1 Pendidikan IPA, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Surabaya, 2023)
The purpose of this research is to describe a strategy for instilling an attitude of caring for the environment through learning natural sciences for junior high school students. The type of research used was descriptive, with the targets being the principal, 1 science teacher, and 6 students. Data collection techniques included learning observation, document analysis, and interviews. The results showed that the habituation method, implemented through science learning, facilitated the instillation of an attitude of caring for the environment. The strategies employed by the teacher included: 1) accustoming students to cleaning the classroom before starting learning, 2) encouraging students to solve problems related to the environment in connection with the learning material, 3) familiarizing students with explanations regarding environmental management, and 4) fostering students' engagement in creating works related to the environment. These findings were supported by interview data, which indicated that science teachers applied a strategy of instilling an attitude of caring for the environment by encouraging students to act and think critically about environmental management.